Pengukuran Kinerja Rantai Pasok di PT XYZ dengan Pendekatan SCOR dan AHP - Elsa Kristy Damanik; Eduart Wolok; Idham Halid Lahay (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
PT XYZ is a manufacturing company that produces foam and spring beds. The company has experienced problems in supply chain management, particularly delays in the delivery of raw materials from suppliers, which have disrupted production activities and hampered the achievement of company targets. This study aims to measure supply chain performance, identify key performance attributes, and formulate recommendations for improvement. Performance measurement was carried out using the Supply Chain Operations Reference (SCOR) model, and attribute weighting was performed using the Analytical Hierarchy Process (AHP) method. The results showed that PT XYZ’s supply chain performance score was 94.58, which is categorized as Excellent. However, indicators such as the timeliness of raw material deliveries, production schedule compliance, and level of production machine damage were still below standard. Recommendations for improvement include improving inventory planning, more efficient production scheduling, and increasing machine reliability.